2019
DOI: 10.12998/wjcc.v7.i2.137
|View full text |Cite
|
Sign up to set email alerts
|

Combination of serum gamma-glutamyltransferase and alkaline phosphatase in predicting the diagnosis of asymptomatic choledocholithiasis secondary to cholecystolithiasis

Abstract: BACKGROUNDGamma-glutamyltransferase (GGT) is one of the most important laboratory tests for the evaluation of liver damage. Through a long-term clinical observation of patients with secondary asymptomatic choledocholithiasis, we found that most patients had abnormal GGT serum levels.AIMTo investigate the combination of serum GGT and alkaline phosphatase (ALP) in predicting the diagnosis of asymptomatic choledocholithiasis secondary to cholecystolithiasis.METHODSIn this retrospective cohort study, the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
3
22
1
1
Order By: Relevance
“… 20 , 22–24 Serum GGT is mainly derived from the liver, primarily distributed in the liver cytoplasm and intrahepatic bile duct epithelium, and excreted by the biliary tract. 25 When biliary obstruction occurs, GGT secreted by biliary epithelial cells and hepatic cells increases; meanwhile, poor bile excretion causes GGT to be absorbed into the bloodstream, leading to the abnormal increase in serum GGT level. Therefore, GGT can clinically be used in the differential diagnosis of biliary obstruction and is able to reflect the degree of biliary obstruction.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 22–24 Serum GGT is mainly derived from the liver, primarily distributed in the liver cytoplasm and intrahepatic bile duct epithelium, and excreted by the biliary tract. 25 When biliary obstruction occurs, GGT secreted by biliary epithelial cells and hepatic cells increases; meanwhile, poor bile excretion causes GGT to be absorbed into the bloodstream, leading to the abnormal increase in serum GGT level. Therefore, GGT can clinically be used in the differential diagnosis of biliary obstruction and is able to reflect the degree of biliary obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…GGT is produced by the hepatocyte mitochondria and confined to the cytoplasm and intrahepatic bile duct epithelium [41]. Previous studies have demonstrated that GGT is significantly and negatively associated with an increase in physical activity [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…GGT participates in oxidative stress and plays a proinflammatory role, leading to the occurrence of various chronic metabolic diseases, and is closely related to the occurrence and development of tumors[ 10 , 11 ]. Serum GGT is mainly secreted from the hepatobiliary system and is excreted by bile[ 12 ]. After biliary obstruction leads to bile drainage obstruction, GGT produced by bile duct epithelial cells and hepatocytes increases, and, due to bile excretion obstruction, GGT enters the blood in reverse flow, and may result in an atypical increase in GGT.…”
Section: Introductionmentioning
confidence: 99%